2011
DOI: 10.1007/s10557-010-6255-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Shows Vasoprotective Effect Reducing Oxidative Stress Without Affecting Metabolic Disturbances in Insulin-dependent Diabetes of Rabbits

Abstract: Overall, there was no noticeable difference between resveratrol treatment groups on the recovery from diabetes. Our results indicate that resveratrol alleviates type 1 diabetes-induced vasculopathy by decreasing vascular oxidative stress and thereby increasing the bioavailability of nitric oxide without changing metabolic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…In this study, there was significant increase in lipid peroxidation in diabetic group which was in agreement with others [22] and [28], resveratrol derivative shows significant value after three weeks of treatment 2.42+0.08 nanomole/ml in comparison with control (2.43+0.2778 nanomole/ml). the concentration of serum MDA in drug (glbcimide ) and purified resveratrol treated rabbits was clarified in Figure (3), the results showed decrease inthe MDA level in diabetic rabbits treated with glbcimide and purified resveratrol to .44+0.1229 nanomole/ml and 2.90+0.05 nanomole/ml respectively after sixth weeks.,.Moreover , following intraperiteal injection of resveratrol , the concentration of MDA in acu-treated rabbits was significantly decreased both in purified resveratrol and resveratrol derivative , which medicates a powerful anti peroxidation effect of resveratrol [28,29]. The results indicate the increased lipid peroxidation under diabetic condition can be due to increased oxidative stress in the cell as a result of depletion of antioxidant protective systems [30,31].…”
Section: Resultssupporting
confidence: 92%
“…In this study, there was significant increase in lipid peroxidation in diabetic group which was in agreement with others [22] and [28], resveratrol derivative shows significant value after three weeks of treatment 2.42+0.08 nanomole/ml in comparison with control (2.43+0.2778 nanomole/ml). the concentration of serum MDA in drug (glbcimide ) and purified resveratrol treated rabbits was clarified in Figure (3), the results showed decrease inthe MDA level in diabetic rabbits treated with glbcimide and purified resveratrol to .44+0.1229 nanomole/ml and 2.90+0.05 nanomole/ml respectively after sixth weeks.,.Moreover , following intraperiteal injection of resveratrol , the concentration of MDA in acu-treated rabbits was significantly decreased both in purified resveratrol and resveratrol derivative , which medicates a powerful anti peroxidation effect of resveratrol [28,29]. The results indicate the increased lipid peroxidation under diabetic condition can be due to increased oxidative stress in the cell as a result of depletion of antioxidant protective systems [30,31].…”
Section: Resultssupporting
confidence: 92%
“…A variety of animals and human studies have shown that short-term resveratrol administration for diabetic subjects (up to two months), could enhance the antioxidant defense, reduce lipid and protein oxidation and decrease apoptosis rate (Kumar et al 2007;Palsamy and Subramanian 2010;Singh et al 2011). The antioxidant property of resveratrol may be performed directly by modulating the antioxidants gene expression and its free radical quenching action or indirectly by reducing of hyperglycemia (Roghani and Baluchnejadmojarad 2010;Akar et al 2011;Yun et al 2011). Moreover, it has been documented that short-term treatment with resveratrol in diabetic subjects has inhibited the activation of NF-κB and the production of NO…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (3,4,5-trihydroxystilbene), a natural bioactive phytochemical mainly found in grapes and berries, has been previously identified as a potent anti-oxidation [14][15][16] and anti-inflammation [17,18] agent. It has been demonstrated that resveratrol possesses broad bioactivities in prevention of cardiovascular disease [19][20][21][22], cancer progression [23][24][25], neurodegenerative disorders [26,27], and metabolic syndrome [28][29][30].…”
Section: Culture and Differentiation Of 3t3-l1 Cellsmentioning
confidence: 99%